Evaluation of Supplemental Energy Source for Grazing Stocker Cattle - L. W. Lomas; J. K. Farney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2018)
Supplementation of grazing cattle is most economically feasible when cattle prices are high relative to the price of grain. Energy supplementation of grazing ruminants may reduce forage intake and digestibility, but energy supplementation at low levels (less than 0.4% bodyweight) has been shown to have little effect on forage intake when crude protein was not limiting. Several studies have evaluated the effect of supplementation on stocker cattle gains and forage utilization during the grazing phase, but few have evaluated the effects of supplementation during the grazing phase on subsequent finishing performance and carcass traits. This research seeks to obtain a more thorough understanding of the interactions among grazing nutrition and management, finishing performance, and carcass traits to facilitate greater economic utilization of these relationships.
Keywords: grazing; stocker cattle; smooth bromegrass; energy; supplementation